The Effect Size of the Science Teachers’ Scientific Method Knowledge on the Planning and Implementing the Scientific Method - Jahidin, Jahidin; Fahyuddin, Fahyuddin; Rabani, La (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
The minimum learning standard in enabling students to be actively involved in building knowledge and skills is the application of the scientific method. The scope of learning activities consists of observing, questioning, experimenting, reasoning, and communicating. The purpose of this study was to discover the effect size of the natural science teachers' scientific method knowledge on the skills of integrating the scientific method in lesson planning and the science teacher's skills in implementing the scientific method in science learning. The study samples were 50 science teachers assigned randomly from 146 junior high school teachers in Kendari City, Indonesia. The scientific method knowledge data collection instrument was a five-step description test of the scientific method whereas data regarding lesson plans were collected using a questionnaire, and learning implementation data used the lesson-plan assessment sheet instrument and the scientific method learning assessment sheet in class. Data were analyzed using a paired samples test statistic in the SPSS version 24 program to determine the effect of knowledge on lesson plans and implementation of the scientific method, while determining the effect size using Cohen's d test. Results showed that the effect size of the scientific method knowledge on learning planning skills was 114 % or large effect, while the effect on the teacher's skills in implementing the scientific method in science learning was 63,2 % or intermediate effect.